Visitors' Perceptions of Service Quality In Taman Eden 100 Agro-Tourism - Donny Ivan Samuel Simatupang; Helena Tatcher Pakpahan; Desyanti Chrismash (International Journal of Science, Technology & Management, 2021)
This study aims to describe the level of visitor satisfaction in Eden 100 Agrotourism based on visitor perceptions, analyze the service performance of Eden 100 Agrotourism Center to influence service quality at Eden 100 Agrotourism Park, and how to improve service quality in Eden 100 Agrotourism Area. purposive, namely in Eden 100 Agrotourism which is located in Lumbanjulu Village, Lumbanrang District, Toba Samosir Regency, North Sumatra Province. This sampling method uses purposive sampling, the sampling technique is not based on random, regional or start, but based on considerations that focus on certain goals. The data analysis method used is a descriptive method and Importance Performance Analysis. The results of the study where the calculations were carried out using the help of SPSS version 15. The results of this study were: 1) The level of suitability of visitors was 73.05%-114.15%, the average level of conformity obtained was 96.53%. The average value of conformity is 17.62% lower than the level of visitor satisfaction which should be 114.15%. In this case, it can be concluded that the level of service performance of Taman Eden Agrotourism 100 is lower than the level of interest or expectations of visitors. 2) Based on the measurement results using Importance Performance Analysis, it can be seen in the Cartesian diagram that the location of items that affect visitor satisfaction with service quality at Taman Eden Agrotourism 100 is divided into four quadrants. 3). Based on the results of the Cartesian diagram, it is known that the service quality dimension attributes that need special attention are in quadrant A (priority) in the context of agro-tourism efforts in improving service quality, including a. the ability of employees to guide visitors which is included in the reliability variable, b. employees are willing to provide fast service which is included in the responsiveness variable, c. the patience of employees in providing services that are included in the guarantee variable, d. employees do not discriminate in serving visitors which are included in the guarantee variable.